"Data and dissertations"-ETD 2016@ Université Lille Nord de France. Issue 10 (7th November 2016) - Ghosh, Maitrayee
Abstract : Purpose: Electronic theses and dissertation (ETD) symposium is one of the major international activities of Networked Digital Library of Theses and Dissertations (NDLTD), and its objectives provide a platform for the exchange of knowledge and skills relevant to ETD students, professors and information professionals. This symposium offers an opportunity to put forward innovative plans, debate on ideas and promote closer cooperation internationally. This report is a summary of selected events held during ETD international symposium 2016 on the theme "Data and Dissertations", with a focus on the handling of research data. Design/methodology/approach: It is a concise review of selected presentations during 19th electronic theses and dissertation annual symposium in University of Lille, France. Findings: ETD 2016 meeting held in Lille was attended by nearly 100 attendees from 28 countries. This report includes a summary of selected presentations on research data, open-access and embargo policies, augmented ETDs and French system for ETDs. It is useful to managers of organizations, teachers and educators, librarians, open-access protagonists and members of information provider communities. The personal interaction with the participants from different countries enriched the author's ideas about the ETD development. Originality/value: The author, who was also a speaker, provides an overview of the selected presentations on the initiatives, namely, research data development, copyright laws, augmented digital theses, plagiarism, etc. The important events such as sight-seeing tours to a national museum, informal get-together are covered which may be useful to the audience who are not able to attend but interested to know about ETD 2016.